Clinical and pathological features of persistent decorative tattoo reactions - José M Suárez-Peñaranda; Carmen Fachal; Maria Blanco-Bellas; Manuel Ginarte; Benigno Monteagudo; Alvaro León; Fernando González-Carril (Wolters Kluwer Medknow Publications, 2022)
Persistent, non-infectious medical complications arising from decorative tattoos have increased considerably. They are difficult to characterize clinically, and histopathology shows a wide variety of overlapping patterns, with lichenoid and granulomatous dermatitis being the most common findings. Both clinical and pathological findings are difficult to ascribe to particular ink colour. The findings in 30 biopsies from 28 patients with persistent reactions in decorative tattoos are reported, including immunohistochemical findings.